2014
DOI: 10.1111/conl.12150
|View full text |Cite
|
Sign up to set email alerts
|

Ambitious Advances of the European Union in the Legislation of Invasive Alien Species

Abstract: Conservation legislation provides a legal basis for conservation action and is crucial for effective conservation management. In April 2014, the European Parliament agreed upon a proposal for an EU‐wide regulation to combat invasive alien species (IAS). The proposal incorporates many Guiding Principles of the Convention on Biodiversity for dealing with IAS. In addition, to prevention, eradication, management, and control it involves scientists, stakeholders and the public in decision making processes. It goes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Invasive ecology because other European policies target invasive species (Beninde et al . ) and A17E takes them as an important threat to habitats (SI‐Table 1‐A4). Definitions of habitats in practitioner's manuals (SI‐Table 1‐A7) are however based on lists of “index species” often including invasive species.…”
Section: Evaluating Hd's Habitat Policymentioning
confidence: 98%
See 1 more Smart Citation
“…Invasive ecology because other European policies target invasive species (Beninde et al . ) and A17E takes them as an important threat to habitats (SI‐Table 1‐A4). Definitions of habitats in practitioner's manuals (SI‐Table 1‐A7) are however based on lists of “index species” often including invasive species.…”
Section: Evaluating Hd's Habitat Policymentioning
confidence: 98%
“…To be able to use these results, practitioners would have to reanalyze raw data to reclassify them in HCI terms, and redo analyses to see whether published results persist when translated (Figure ). Invasive ecology because other European policies target invasive species (Beninde et al . ) and A17E takes them as an important threat to habitats (SI‐Table 1‐A4). Definitions of habitats in practitioner's manuals (SI‐Table 1‐A7) are however based on lists of “index species” often including invasive species.…”
Section: Evaluating Hd's Habitat Policymentioning
confidence: 99%
“…Risk assessment is essential for underpinning many components of IAS policy, for example EU Regulation No 1143/2014, and decision‐making including prevention (to inform legislation and justify restrictions, such as on trade and/or consumer activities), early detection (warning) and rapid response (prioritizing action and guiding surveillance) and long‐term control (prioritizing species for control and monitoring) (Beninde, Fischer, Hochkirch, & Zink, ; Genovesi, Carboneras, Vilà, & Walton, ; Tollington et al., ). Additionally, risk assessments are required to justify measures that may affect trade without infringing the rules and disciplines of the World Trade Organisation (WTO) (Shine et al., ) and for communicating with other sectors such as those with conservation remits (Pergl et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all Member States must aim at recovering costs undergone to prevent, minimise and mitigate the negative impacts brought by invasive alien species, as well as cost related to habitat restoration. As stated by Beninde et al (2014) payments must be covered by human beings or legal person found to be the cause of the introduction or spread of invasive alien species. These authors also highlighted that in this way society as a whole will not bear the costs of these activities.…”
Section: Polluter Pays Principlementioning
confidence: 99%